Natural History of Paclitaxel-associated Acute Pain Syndrome: A Case Report of Rare Side Effect of Paclitaxel - Salima, Siti; Budi Harsono, Ali; Aisyah, Aisyah; Mantilidewi, Kemala (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: One of the harshest side effects following anticancer agent treatments is chemotherapy-induced neuropathic pain. After surgical staging, chemotherapy combination of paclitaxel carboplatin could be a choice of therapy for Stage II or more advanced stage of ovarian cancer. Different side effects may appear after the application of paclitaxel. CASE REPORT: Here, we show an uncommon case of paclitaxel-acute pain syndrome (P-APS), and how we deal with such cases according to our experiences. One uncommon side effect is P-APS, which can be treated effectively with the administration of non-steroidal anti-inflammatory drugs, corticosteroid, and supportive therapy. CONCLUSION: One uncommon side effect of Paclitaxel induced neuropathic can be treated effectively with the administration of non-steroidal anti inflammatory drugs, corticosteroid, and supportive therapy.